Creative Drama Based Active Learning Implementation in In-Service Training - Sarisoy, Baris; Alci, Bulent (DERGIPARK AKAD, 2021)
This study aims to enable teachers who have not had any previous experience with creative drama to experience an active learning experience created with the creative drama method and consult their creative drama views, an active learning method. A ten-hour creative drama-based active learning in-service training for teachers was designed and implemented based on this aim. The implementation was carried out in a school in Istanbul in the 2019-2020 academic year, and five preschools, 12 primary schools, and 19 secondary school teachers working in this school participated in the implementation. The mixed research design was chosen as the research design of the study. Within the scope of qualitative data collection and analysis of the study, participants' opinions about creative drama were taken during and after the in-service training implementation. These collected data were analyzed and interpreted through content analysis. In the quantitative part, the acquisition evaluation form, which was designed to examine the change in the participants' knowledge levels regarding the active learning model, techniques, and implementation forms in the educational content, was applied as the pre-post-test. The data obtained from the form were analyzed through the SPSS 22.0 program Wilcoxon Signed Rankings Test, and it was evaluated to see whether there was a statistically significant difference between pre-test and post-test results. On the other hand, the in-service training program evaluation form was used to get the participants' opinions about the training at the end of the training. As a result of the study, it was revealed that there was a significant difference between the achievement evaluation form pre-test post-test scores of the participants. They found the in-service training practical and useful and developed a positive perception of the creative drama method.
Keywords: Active learning; creative drama; in-service training; mixed research; Education & Educational Research